Improving the physiological status of broiler chickens using rosemary leaf meal and sodium bentonite as ammonia gas control agents - Mercy Chisara Ogwuegbu; Fredrick Ugochukwu Udeh; Josephine Chinenye Ugwuozor; Precious Ezinne Okoye; Joy Chimela Kalu; Emmanuel Chinonso Arum; Doctor Mziwenkosi Nhlanhla Mthiyane (Journal of Applied Animal Research)
As the poultry industry shifts towards natural antibiotic-free alternatives, rosemary leaf meal (RLM) and sodium bentonite (SB) have emerged as promising dietary supplements for enhancing broiler physiological status, meat quality, and environmental management. This study evaluated the effects of RLM and SB inclusion on broiler physiological status, meat quality and litter ammonia levels. A total of 360 male Cobb 500-day-old broilers were randomly allotted into 6 dietary treatments in a 2 × 3 factorial arrangement, with 6 replicates of 10 birds each in a completely randomized design (CRD). Dietary treatments included: T1: (0 g RLM + 0 g SB/kg diet), T2: (3 g RLM + 0 g SB/kg diet), T3: (6 g RLM + 0 g SB/kg diet), T4: (0 g RLM + 15 g SB/kg diet), T5: (3 g RLM + 15 g SB/kg diet), T6: (6 g RLM + 15 g SB/kg diet), respectively, and were fed for 42 days. Data were analyzed using two-way ANOVA, and significant differences were determined using Duncan's New Multiple Range Test. A Student's t-test was used for comparisons between two treatment groups. Broilers fed 6 g RLM + 15 g SB/kg diet exhibited significantly (P < 0.05) enhanced antioxidant enzyme activities (superoxide dismutase, catalase, glutathione peroxidase and glutathione reductase), reduced malondialdehyde and cholesterol levels, and improved mineral composition (potassium, calcium, magnesium, zinc, iron, and phosphorus). Meat quality parameters such as redness, yellowness and water holding capacity improved significantly (P < 0.05), while lightness, driploss, and litter ammonia levels decreased. In conclusion, the combination of 6 g RLM + 15 g SB/kg in broiler diets optimizes oxidative status, mineral composition, meat quality and environmental sustainability.